Strut efficiency factors for structural concrete made from coarse recycled concrete aggregates - Sahoo, Dipak Kumar; Singh, Bhupinder; Bhargava, Pradeep (Journal of Structural Engineering, 2025)
The test results of sixteen reinforced concrete beams, fourteen made from concrete containing coarse recycled concrete aggregates (RCA) and two from concrete containing natural coarse aggregates, reported recently in the literature, have been reanalysed using the strut-and-tie method and efficiency factors of concrete struts in the sixteen beams have been calculated and compared with the values recommended for struts made of conventional natural aggregate concrete in ACI 318-08 Appendix-A and in the literature. The analysis suggests that in terms of strut efficiency factors, the strengths of the struts in the RCA-concrete beams were in no way inferior to that of the struts in the natural coarse aggregate concrete beams. This investigation reaffirms that if a proper mix proportioning method is adopted to account for the presence of residual mortar in the coarse recycled concrete aggregates, structural concrete made from these waste materials can be designed using the strut-and-tie method to have the same strength characteristics as conventional concrete made of natural coarse aggregates. The analysis also highlights the unconservatism in the ACI strut efficiency factors for structural concrete irrespective of the type of aggregates in the concrete.